2021
DOI: 10.1159/000519407
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Endoscopy

Abstract: <b><i>Background:</i></b> Owing to their rapid development, artificial intelligence (AI) technologies offer a great promise for gastroenterology practice and research. At present, AI-guided image interpretation has already been used with success for endoscopic detection of early malignant lesions. Nonetheless, there are complex challenges and possible shortcomings that must be considered before full implementation can be realized. <b><i>Summary:</i></b> In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…ADR is one of the most common outcome indicators used to assess the quality of colonoscopy for many years. [29] Several published systematic reviews and meta-analyses [30][31][32] have shown a significant increase in ADR in AIAC compared to conventional colonoscopy. Several studies showed that the colonic blind spot is an important factor to reduce the detection rate of colorectal lesions, [15] while, AI real-time polyp and adenoma detection system based on convolutional neural network neural network can detect colorectal lesions that cannot be seen by human eyes and improve ADR.…”
Section: Discussionmentioning
confidence: 99%
“…ADR is one of the most common outcome indicators used to assess the quality of colonoscopy for many years. [29] Several published systematic reviews and meta-analyses [30][31][32] have shown a significant increase in ADR in AIAC compared to conventional colonoscopy. Several studies showed that the colonic blind spot is an important factor to reduce the detection rate of colorectal lesions, [15] while, AI real-time polyp and adenoma detection system based on convolutional neural network neural network can detect colorectal lesions that cannot be seen by human eyes and improve ADR.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of artificial intelligence (AI) models for diagnosing medical conditions could reduce the burden on healthcare professionals and prevent oversights by alleviating the problem that traditional diagnoses are examiner-dependent [ 17 ]. There has already been success in utilizing AI for endoscopy, chest X-rays, and pathological examinations [ [18] , [19] , [20] , [21] ]. It has been reported that various AI models can facilitate clinical care for professionals, improving diagnosis and treatment for people with hemophilia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This essentially serves to standardize, improve the detection of pathological findings, and accelerate diagnostics. In their review articles on Artificial Intelligence in Endoscopy [13] and Advances in Digital Pathology [14], the authors Hann and Meining as well as Grosserüschekamp et al [14] summarize the current status of the development and the beginning translation into clinical studies and routine.…”
mentioning
confidence: 99%